2016
DOI: 10.1553/giscience2016_02_s134
|View full text |Cite
|
Sign up to set email alerts
|

The GI-Learner Approach: Learning Lines for Geospatial Thinking in Secondary Schools

Abstract: This paper introduces basic considerations that inform education for geospatial thinking, as proposed in the KA2 Erasmus Plus GI-Learner project. It reports on some initial state-of-theart activities of the project, presents a list of GI-Learner competences based on a broad literature review and establishes a roadmap for future support activities for geospatial learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Obtaining data from the SDIs and integrating them into the Geographic Information Systems on the cloud or WebGIS is of great assistance for these objectives in education [13][14][15][16][17][18], because it is an excellent field for the active teaching of the use of collaborative working techniques, and it also leads to the benefits that the TPACK promotes. It has been shown that a WebGIS reinforces learning and is integrated into a novel educational current whose success in the classroom has been noted by numerous authors [19][20][21][22][23][24][25][26][27].…”
Section: The Wealth Of Data Of the Spatial Data Infrastructures For Addressing The Sustainable Development Goalsmentioning
confidence: 99%
“…Obtaining data from the SDIs and integrating them into the Geographic Information Systems on the cloud or WebGIS is of great assistance for these objectives in education [13][14][15][16][17][18], because it is an excellent field for the active teaching of the use of collaborative working techniques, and it also leads to the benefits that the TPACK promotes. It has been shown that a WebGIS reinforces learning and is integrated into a novel educational current whose success in the classroom has been noted by numerous authors [19][20][21][22][23][24][25][26][27].…”
Section: The Wealth Of Data Of the Spatial Data Infrastructures For Addressing The Sustainable Development Goalsmentioning
confidence: 99%
“…Also, Rubino-Hare et al (2016) emphasize that the use of GST as a pedagogical tool takes 1 to 2 years in continuous learning. Therefore, Pre-service and experienced geography teachers focus on learning about GST and how to teach it (Donert et al, 2016;Zwartjes & de Lázaro y Torres, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Геокеңістіктік технологиялар географиялық масштабтарды (жергілікті, аймақтық, ұлттық және жаһандық), кеңістіктік талдауды және зерттеулерді, сонымен қатар нақты ГАЖ ғылымын және құралдарын қамтиды. Осылайша, Америка Құрама Штаттарында және Еуропа елдерінде география сыныптарындағы күнделікті іс-әрекеттер үшін кеңістіктік ойлауды дамыту үшін геокеңістіктік технологияларды пайдалануды ұсынады (Donert & etc., 2016) [16].…”
Section: әдебиеттерге шолуunclassified